Regeneration and Endogenous Phytohormone Responses to High-Temperature Stress Drive Recruitment Success in Hemiepiphytic Fig Species - Fang, Chuangwei; Chen, Huayang; Castillo-Díaz, Diana; Wen, Bin; Cao, Kun-Fang; Goodale, Uromi Manage (Frontiers in Plant Science, 2021)
Exposure to high temperature stress (HTS) during early regeneration in plants can profoundly shape seed germination, seedling growth and development, providing stress resilience. We assessed how the timing of HTS, implemented as eight hours in 40 ºC, affects the early regeneration stages and phytohormone concentration of four hemiepiphytic (Hs) and four non-hemiepiphytic (NHs) Ficus species. Their seed germination, seedling emergence and seedling survival probabilities and the concentrations of three endogenous phytohormones, abscisic acid (ABA), indole-3-acetic acid (IAA) and salicylic acid (SA) were assessed after HTS imposed during imbibition, germination and emergence. In both groups, seeds were more sensitive to HTS in the early regeneration process; stress experienced during imbibition affected emergence and survival and stress experienced during germination affected subsequent emergence. There was no effect from HTS when received after emergence. Survival was highest in hemiepiphytes regardless of the HTS treatment. The phytohormones showed growth form- and regeneration stage-specific responses to HTS; due to the HTS treatment both SA and ABA levels decreased in non-hemiepiphytes during imbibition and germination and during germination IAA increased in hemiepiphytes but was reduced in non-hemiepiphytes. Due to the HTS treatment experienced during emergence ABA and IAA concentrations were greater for hemiepiphytes but an opposite effect was seen in the two growth forms for the SA concentration. Our study shows that the two growth forms have different strategies for regulating their growth and development in the early regeneration stages in order to respond to HTS. The ability to respond to HTS is an ecologically important functional trait that allows plant species to appropriately time their seed germination and seedling development. Flexibility in modulating species regeneration in response to HTS in these subtropical and tropical Ficus species could provide greater community resilience under climate change.